2017
DOI: 10.1097/scs.0000000000003594
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood in Pediatric Craniofacial Reconstruction Surgery

Abstract: There was no postoperative coagulopathy in the WB cohort. Whole blood was also associated with significantly fewer perioperative BDEs. Whole blood appears to be as effective as RB for replacement of blood loss in craniofacial surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…This conflicts with the results of a prior retrospective study conducted at our institution of 111 patients who received either whole blood or donor-matched reconstituted blood (consisting of pRBCs and FFP from the same blood donor) due to an institutional practice change. 5 It is possible that our study was insufficiently powered to detect a difference in the number of blood donor exposures or that surgical technique modifications over the time period contributed to the findings from the prior study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This conflicts with the results of a prior retrospective study conducted at our institution of 111 patients who received either whole blood or donor-matched reconstituted blood (consisting of pRBCs and FFP from the same blood donor) due to an institutional practice change. 5 It is possible that our study was insufficiently powered to detect a difference in the number of blood donor exposures or that surgical technique modifications over the time period contributed to the findings from the prior study.…”
Section: Discussionmentioning
confidence: 90%
“…(pRBCs), 4 the use of whole blood in place of blood component therapy, 5 use of pRBCs and fibrinogen concentrate, 6,7 or prophylactic fibrinogen infusion. 8 One potential strategy to evaluate current blood management strategies is viscoelastic testing with the thromboelastography (TEG) assay (TEG, Haemonetics, Boston, MA), or the rotational thromboelastography (ROTEM) assay.…”
mentioning
confidence: 99%
“…In 2014, the US Tactical Combat Casualty Care Committee recommended whole blood as the optimal product for resuscitation in combat casualty care of massive hemorrhage . Low‐titer group O whole blood has had promising use in civilians also, including use in children with massive hemorrhage or during craniofacial or other surgeries where blood loss is significant …”
Section: Discussionmentioning
confidence: 99%
“…The strengths of this QI initiative include the large number of patients, a long duration of follow-up, the discrete interventions, and a systematic prospective data capture. Although we have previously described the outcomes of these interventions, 1,3,[5][6][7][8][9][10][11] the authors of those studies did not report on our "real world" experience of caring for this population because they excluded patients who were not receiving the designated interventions. The data we have presented provide insight into the summative effect of these sequential improvement efforts.…”
Section: Limitationsmentioning
confidence: 99%
“…We have demonstrated that monitoring central venous pressure is not an accurate measure of volume status in CCVR surgery, 6 that reconstituted blood 7 and antifibrinolytics 3 can reduce blood loss and donor exposures, that the use of postoperative transfusion guidelines can lead to a more rational postoperative transfusion practice, 8 and that whole blood provides some unique advantages in terms of limiting the incidence of perioperative coagulopathy in patients who are undergoing CCVR. 9 All of these studies were conducted as retrospective case-control studies with specific inclusion and exclusion criteria. However, we have not analyzed the summative effects of our interventions over time in our entire craniofacial population nor have we evaluated the impact of these interventions on total perioperative blood transfusion rates.…”
mentioning
confidence: 99%